Structural battery based on shape memory composite material and preparation method thereof
By using shape memory composite materials in structural batteries, the bend and reversible reconstruction of the battery are achieved, solving the problem that existing structural batteries cannot meet complex shape conditions, and improving the mechanical strength and energy storage characteristics of the battery.
Patent Information
- Application Number
- CN202411750656.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-08
AI Technical Summary
Existing structural batteries cannot achieve bending and reversible reconstruction, and it is difficult to meet the structural-energy storage integration needs of complex shape conditions.
The structural battery design based on shape memory composite material is adopted, including a structural/negative electrode integrated layer, a separator layer, a positive electrode layer, a functional electrolyte and a packaging layer, and the bending and reversible reconstruction of the battery is achieved through the temperature-driven deformation function.
The bending and reversible reconstruction functions of structural batteries are realized, the mechanical strength and energy storage characteristics of the batteries are improved, and a new integrated structural energy storage solution is provided.
Smart Images

Figure CN119786616A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a structural battery based on a shape memory composite material and a preparation method thereof. Background Art
[0002] As an energy storage device that can withstand structural loads and replace structural components, structural batteries can reduce the weight of the entire system and increase driving range. Since structural batteries can be distributed throughout the main body rather than concentrated in the same location, this distributed energy storage design greatly improves the design space and safety of the entire system. In recent years, structural energy storage composite materials with carbon fiber as a carrier have attracted the interest of many scholars. By utilizing the excellent mechanical properties of carbon fiber, the structural parts and energy storage systems are combined into one, which can effectively save load space, reduce system weight, and increase battery energy density. It has become a new research hotspot at home and abroad.
[0003] In order to solve the battery structural problem, researchers have proposed a variety of solutions. At present, there are two main methods for constructing structural batteries: (1) encapsulating general batteries in lightweight and strong reinforcing materials; (2) introducing high mechanical and strong functional materials as internal components and components of the battery. The first is to sandwich the battery between strong external reinforced composite materials at the battery level. In this design, the external reinforced composite material is mainly responsible for mechanical bearing and does not participate in energy storage. The battery is mainly used as an energy storage part and only bears limited loads. Although this strategy has good compatibility with existing battery and composite mass production, it has limited weight savings and batteries without mechanical strength often become mechanical weak points, which will greatly reduce the mechanical properties of the composite. The second is to introduce high-strength functional materials at the material level to improve the intrinsic mechanical properties of battery components, replace structural components, reduce system weight and improve overall endurance. Common strategies include using carbon fibers as high-strength current collectors and electrodes, using solid electrolytes to enhance mechanical properties, and using mechanically strong diaphragms.
[0004] The Chinese invention patent application (publication number: CN111211330A) discloses a flexible lithium-ion battery with high room temperature ionic conductivity and easy production, and a preparation method thereof, wherein a conductive silver layer is coated on a porous mesh film to form a current collector, and elastic positive electrode materials and elastic negative electrode materials are sprayed to form positive electrode layers and negative electrode layers. Although the battery can be bent, its mechanical properties are poor and it cannot be used to carry components.
[0005] Based on the existing construction method, the structural battery has a single structure, and it is impossible to achieve bending and reversible reconstruction of the structural battery, which makes it difficult to meet the structural-energy storage integration requirements of complex shape conditions. Summary of the invention
[0006] The purpose of the present invention is to solve the problems of battery structuring and structural functionalization, and to provide a structural battery based on shape memory composite materials to achieve the bending and reversible reconstruction of the structural battery.
[0007] In order to achieve the above object, the present invention provides a structural battery based on a shape memory composite material, characterized in that it includes a structure / negative electrode integrated layer, a separator layer, a positive electrode layer, a functional electrolyte, and a packaging layer.
[0008] The structure / negative electrode integrated layer is formed by loading the negative electrode material on the shape memory composite material matrix;
[0009] The diaphragm layer is a high temperature resistant diaphragm;
[0010] The positive electrode layer is a positive electrode sheet with a self-modified surface;
[0011] The functional electrolyte is a high temperature resistant electrolyte;
[0012] The packaging layer is an aluminum-plastic film.
[0013] Furthermore, the structure / negative electrode integrated layer is formed by compounding a shape memory polymer on one side of a carbon fiber matrix and compounding a negative electrode material on the other side.
[0014] Furthermore, the negative electrode material is a silicon-containing negative electrode material, and the silicon-containing negative electrode material is a silicon-graphite composite material with a silicon content of 5 to 70 wt%.
[0015] Furthermore, the high temperature resistant diaphragm layer is any one selected from the group consisting of in-situ self-assembled surface-modified polyolefin diaphragms, aramid diaphragms, polyimide diaphragms, and glass fiber diaphragms.
[0016] Furthermore, the positive electrode layer is formed by preparing a coating layer on the surface of the positive electrode plate through atomic level regulation, and the coating layer is any one of a TiO2 coating layer, an AlPO3 coating layer, and an Al2O3 coating layer.
[0017] Furthermore, the positive electrode material of the positive electrode plate is a layered positive electrode material, a phosphate positive electrode material, or a spinel positive electrode material.
[0018] Furthermore, the functional electrolyte is a combination of any one or more selected from solvents containing fluorinated ethers, fluorinated carboxylates, fluorinated carbonates, nitrile compounds, etc.; the lithium salt in the functional electrolyte is a combination of any one or more selected from LiFSI, LiTFSI, LiDFOB, LiPF6, LiBF4, LiBOB; the additive in the functional electrolyte is a combination of any one or more selected from PFN, TEOSCN, TPFPB, TMSB, etc.
[0019] The present invention also provides a method for preparing the above-mentioned structural battery based on the shape memory composite material, characterized in that it comprises the following steps:
[0020] Step 1, preparing battery cells by a "Z"-shaped lamination method, and performing welding and packaging;
[0021] Step 2: After the battery is filled, formed, and divided into different capacities, the battery is heated to a certain temperature and left for a certain period of time, and a mold with a certain curvature is used to pressurize the battery to obtain a structural battery with a controllable shape;
[0022] Step 3, heating the controllable shape structure battery to a certain temperature and leaving it for a certain time, applying pressure, and obtaining a planar structure battery;
[0023] Step 4: By repeating the heating and pressurizing process, structural batteries with different curvatures are obtained.
[0024] Furthermore, in step 1, the electrode is coated intermittently, the coating area is adjusted according to the actual application situation, and there is a blank foil area between each electrode layer.
[0025] Furthermore, in steps 2 and 3, the heating temperature ranges from 60° C. to 120° C., and the standing time ranges from 2 min to 30 min.
[0026] Beneficial effects of the present invention:
[0027] The present invention prepares a bendable and reconfigurable structural battery based on shape memory composite materials. Under the stimulation of a specific temperature environment, stress is applied to the battery to bend and deform. After the temperature drops, the mechanical strength of the battery increases, and the shape-keeping characteristics of the battery are realized. Similarly, under the stimulation of a specific temperature environment, the bent battery can be deformed into a flat structure and bend again into a different shape. After the temperature drops, it continues to maintain its shape, thereby realizing the bending shape-keeping and reversible reconstruction functions of the battery, and constructing a new method of "structuring of batteries" and "functionalization of structures". BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of a flat-plate battery and its cross-sectional structure according to Embodiment 1 of the present invention.
[0029] Figure 2 Schematic diagram of a curved battery and cross-sectional structure according to Example 2 of the present invention.
[0030] Figure 3 This is the charge and discharge curve of the battery structure before and after bending of Example 3 of the present invention.
[0031] Figure 4 This is the battery cycle curve of the structure before and after bending of Example 4 of the present invention. DETAILED DESCRIPTION
[0032] The specific implementation of the present invention will be further described below in conjunction with the accompanying drawings.
[0033] The structural battery based on shape memory composite material described in the present invention is different from conventional composite material reinforced batteries, such as encapsulating general batteries in lightweight and strong reinforcing materials, or introducing high mechanical and strong functional materials as internal components and assemblies of batteries, in which the composite material only has a reinforcing effect, while the composite material in the present invention has both structural and deformation functions.
[0034] The present invention realizes the fusion of structural components and battery components through the reinforcement and deformation functions of shape memory composite materials and the deformation and shape preservation of structural batteries under temperature driving, and proposes a new method for constructing structural batteries.
[0035] The present invention provides a structural battery based on a shape memory composite material, which comprises a structure / negative electrode integrated layer, a separator layer, a positive electrode layer, a functional electrolyte, a packaging layer, etc.
[0036] The structure / negative electrode integrated layer is formed by loading the negative electrode material on the shape memory composite material matrix. In one embodiment, the structure / negative electrode integrated layer of the present invention is formed by compounding the shape memory polymer on one side of the carbon fiber matrix and compounding the negative electrode material on the other side. The negative electrode material can be a silicon-containing negative electrode material. The silicon-containing negative electrode material can be a silicon-graphite composite material with a silicon content of 5 to 70wt%.
[0037] The diaphragm layer is composed of a high temperature resistant diaphragm, which can be any one selected from in-situ self-assembled surface-modified polyolefin diaphragms, aramid diaphragms, polyimide diaphragms, glass fiber diaphragms, and the like.
[0038] The positive electrode layer is a positive electrode sheet with a self-modified surface. In one embodiment, the positive electrode layer is a coating layer prepared by atomic level regulation on the surface of the positive electrode sheet. The positive electrode material can be a layered positive electrode material, a phosphate positive electrode material, or a spinel positive electrode material. The coating layer can be any one of a TiO2 coating layer, an AlPO3 coating layer, and an Al2O3 coating layer.
[0039] The functional electrolyte is a high temperature resistant electrolyte. The functional electrolyte can be a combination of any one or more selected from solvents such as fluorinated ethers, fluorinated carboxylates, fluorinated carbonates, nitrile compounds, etc. The lithium salt in the functional electrolyte can be a combination of any one or more selected from LiFSI, LiTFSI, LiDFOB, LiPF6, LiBF4, LiBOB, etc. The additive in the functional electrolyte can be a combination of any one or more selected from PFN, TEOSCN, TPFPB, TMSB, etc.
[0040] The packaging layer is an aluminum-plastic film.
[0041] The present invention realizes the bending and reversible reconstruction functions of the structural battery through temperature drive of the shape memory composite material.
[0042] The present invention also provides a method for preparing the above-mentioned structural battery based on the shape memory composite material, comprising the following steps:
[0043] Step 1: Prepare the battery cell by "Z"-shaped lamination, and perform welding and packaging. The electrode is coated intermittently, and the coating area is adjusted according to the actual application situation. There is a blank foil area between each electrode layer;
[0044] Step 2: After the battery is filled, formed, and divided, the battery is heated to a certain temperature and left for a certain time, and a mold with a certain curvature is used to press the battery to obtain a structural battery with a controllable shape. The heating temperature range is 60℃~120℃, and the leaving time is 2min~30min.
[0045] Step 3, heating the controllable shape structure battery to a certain temperature and leaving it for a certain time, applying pressure, and obtaining a planar structure battery. The heating temperature range is 60°C to 120°C, and the leaving time is 2min to 30min.
[0046] Step 4: By repeating the heating and pressing process, structural batteries with different curvatures can be obtained.
[0047] In the present invention, the battery is initially flat, then can be bent into a curved surface, can then be restored to a flat surface, and can then be bent into a curved surface again, which is a repeatable process.
[0048] Example
[0049] Example 1
[0050] The positive electrode material is LiNi 0.8 Co 0.1 Mn 0.1 O2, atomic-level regulation is used to prepare the positive electrode material Al2O3 coating layer, and the negative electrode material is a silicon-graphite composite material with a silicon content of 15wt%. The pole piece is coated intermittently, and there is a blank foil area between each pole piece coating. A carbon fiber matrix is used to composite shape memory material on one side and load negative electrode material on the other side to prepare a structural / negative electrode integrated layer. A "Z"-shaped stacking method is used, and the electrolyte uses a fluorocarbonate-based electrolyte containing LiPF6 to prepare the battery cell, and welding, packaging, injection, formation, and capacity division are carried out to obtain a planar battery, whose structure is as follows Figure 1 shown.
[0051] Example 2
[0052] The positive electrode material is LiNi 0.8 Co0.1 Mn 0.1 O2, atomic-level regulation is used to prepare the Al2O3 coating layer of the positive electrode material, and the negative electrode material is a silicon-graphite composite material with a silicon content of 15wt%. The pole piece is coated intermittently, and there is a blank foil area between the coatings of each pole piece. A carbon fiber matrix is used to composite shape memory material on one side and load the negative electrode material on the other side to prepare a structural / negative electrode integrated layer. A "Z"-shaped stacking method is adopted, and the electrolyte uses a fluorocarbonate-based electrolyte containing LiPF6, and the additive is PFN. The battery cell is prepared, and welding, packaging, injection, formation, and capacity division are carried out to obtain a planar battery. After the planar battery is placed at 80°C for 5 minutes, a mold is used to press the planar battery to obtain a curved battery, and its structure is as follows Figure 2 shown.
[0053] Example 3
[0054] The positive electrode material is LiNi 0.9 Co 0.05 Mn 0.05 O2, atomic-level regulation is used to prepare the positive electrode material AlPO3 coating layer, and the negative electrode material is a silicon-graphite composite material with a silicon content of 20wt%. The pole piece is coated intermittently, and there is a blank foil area between each pole piece coating. A carbon fiber matrix is used to composite shape memory material on one side and load negative electrode material on the other side to prepare a structural / negative electrode integrated layer. A "Z"-shaped stacking method is adopted, and the electrolyte uses a fluorocarboxylic acid ester-based electrolyte containing LiFSI to prepare the battery cell, and welding, packaging, injection, formation, and capacity division are carried out to obtain a planar battery. After the planar battery is placed at 85°C for 5 minutes, a mold is used to pressurize the planar battery to obtain a bent battery, and its mechanical properties are tested. The battery modulus is 6.8GPa, the bending strength is 180MPa, and the elongation at break is 30%. The charge and discharge performance of the battery before and after bending is also tested, such as Figure 3 As shown, the battery capacity retention rate after bending is 96.7%.
[0055] Example 4
[0056] The positive electrode material is LiNi 0.9 Co 0.05 Mn 0.05O2, atomic-level regulation is used to prepare the positive electrode material TiO2 coating layer, and the negative electrode material is a silicon-graphite composite material with a silicon content of 30wt%. The pole piece is coated intermittently, and there is a blank foil area between the coatings of each pole piece. A carbon fiber matrix is used to composite shape memory material on one side and load the negative electrode material on the other side to prepare a structural / negative electrode integrated layer. A "Z"-shaped stacking method is adopted, and the electrolyte uses a fluorinated carboxylic acid ester-based electrolyte containing LiFSI and LiDOFB to prepare battery cells, and then weld, package, inject, form, and divide the capacity to obtain a planar battery. After the planar battery is placed at 70°C for 20 minutes, a mold is used to pressurize the planar battery to obtain a curved battery, and the cycle performance of the battery before and after bending is tested, such as Figure 4 As shown, the planar battery has a capacity retention rate of 81.7% after 150 cycles under normal temperature and 0.3C charge and discharge conditions, and the curved battery has a capacity retention rate of 73.4% after 150 cycles under normal temperature and 0.3C charge and discharge conditions.
[0057] Theoretically, any lithium-ion battery system can be applied to the structural battery of the present invention.
[0058] The structural battery based on shape memory composite material provided by the present invention can realize bending and reversible reconstruction of the structural battery under temperature drive. Different from the reinforcement effect of traditional composite materials, the structural battery of the present invention has both high strength and energy storage characteristics, and proposes a new idea for constructing integrated structural energy storage.
[0059] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A structural battery based on shape memory composite material, characterized in that: It includes a structure / negative electrode integrated layer, a separator layer, a positive electrode layer, a functional electrolyte, and a packaging layer. The structure / negative electrode integrated layer is formed by loading the negative electrode material on the shape memory composite material matrix; The diaphragm layer is a high temperature resistant diaphragm; The positive electrode layer is a positive electrode sheet with a self-modified surface; The functional electrolyte is a high temperature resistant electrolyte; The packaging layer is an aluminum-plastic film.
2. The structural battery based on shape memory composite material according to claim 1, characterized in that: The structure / negative electrode integrated layer is formed by compounding a shape memory polymer on one side of a carbon fiber matrix and compounding a negative electrode material on the other side.
3. The structural battery based on shape memory composite material according to claim 1, characterized in that: The negative electrode material is a silicon-containing negative electrode material, and the silicon-containing negative electrode material is a silicon-graphite composite material with a silicon content of 5 to 70 wt%.
4. The structural battery based on shape memory composite material according to claim 1, characterized in that: The high temperature resistant diaphragm layer is any one selected from a polyolefin diaphragm, an aramid diaphragm, a polyimide diaphragm and a glass fiber diaphragm with in-situ self-installed surface modification.
5. The structural battery based on shape memory composite material according to claim 1, characterized in that: The positive electrode layer is formed by preparing a coating layer on the surface of the positive electrode plate through atomic level regulation, and the coating layer is any one of a TiO2 coating layer, an AlPO3 coating layer, and an Al2O3 coating layer.
6. The structural battery based on shape memory composite material according to claim 1, characterized in that: The positive electrode material of the positive electrode plate is a layered positive electrode material, a phosphate positive electrode material, or a spinel positive electrode material.
7. The structural battery based on shape memory composite material according to claim 1, characterized in that: The functional electrolyte is a combination of any one or more solvents selected from fluorinated ethers, fluorinated carboxylates, fluorinated carbonates, nitrile compounds, etc.; the lithium salt in the functional electrolyte is a combination of any one or more selected from LiFSI, LiTFSI, LiDFOB, LiPF6, LiBF4, LiBOB; the additive in the functional electrolyte is a combination of any one or more selected from PFN, TEOSCN, TPFPB, TMSB, etc.
8. The method for preparing a structural battery based on a shape memory composite material according to any one of claims 1 to 7, characterized in that: The following steps are included: Step 1, using a "Z"-shaped stacking method to prepare battery cells, and then welding and packaging them; Step 2: After the battery is filled, formed, and divided into different capacities, the battery is heated to a certain temperature and left for a certain period of time, and a mold with a certain curvature is used to pressurize the battery to obtain a structural battery with a controllable shape; Step 3, heating the controllable shape structure battery to a certain temperature and leaving it for a certain time, applying pressure, and obtaining a planar structure battery; Step 4: By repeating the heating and pressurizing process, structural batteries with different curvatures are obtained.
9. The preparation method according to claim 8, characterized in that: In step 1, the electrode is coated intermittently, and the coating area is adjusted according to the actual application situation. There is a blank foil area between each electrode layer.
10. The preparation method according to claim 8, characterized in that: In steps 2 and 3, the heating temperature ranges from 60° C. to 120° C., and the standing time ranges from 2 min to 30 min.
Citation Information
Patent Citations
Bendable lithium ion battery and manufacturing method thereof
CN111211330A
Soft-package ternary power battery and preparation method thereof
CN107256971A
Low-cost and stable lithium battery silicon negative electrode and preparation method thereof
CN109671913A
Negative electrode and battery
JP2005141995A